Approximate N3LO Higgs-boson production cross section using physical-kernel constraints - de Florian, Daniel Enrique (2014)
The single-logarithmic enhancement of the physical kernel for Higgs production by gluon-gluon fusion in the heavy top-quark limit is employed to derive the leading so far unknown contributions, ln 5, 4, 3(1−z), to the N3LO coefficient function in the threshold expansion. Also using knowledge from Higgs-exchange DIS to estimate the remaining terms not vanishing for z = mH2 /s? → 1, these results are combined with the recently completed soft+virtual contributions to provide an uncertainty band for the complete N3LO correction. For the 2008 MSTW parton distributions these N3LO contributions increase the cross section at 14 TeV by (10 ± 2)% and (3 ± 2.5)% for the standard choices μR = mH and μR = mH /2 of the renormalization scale. The remaining uncertainty arising from the hard-scattering cross sections can be quantified as no more than 5%, which is smaller than that due to the strong coupling and the parton distributions.